2019
DOI: 10.1093/jac/dkz309
|View full text |Cite
|
Sign up to set email alerts
|

A prophage and two ICESa2603-family integrative and conjugative elements (ICEs) carrying optrA in Streptococcus suis

Abstract: Objectives To investigate the presence and transfer of the oxazolidinone/phenicol resistance gene optrA and identify the genetic elements involved in the horizontal transfer of the optrA gene in Streptococcus suis. Methods A total of 237 S. suis isolates were screened for the presence of the optrA gene by PCR. Whole-genome DNA of three optrA-positive strains was completely sequenced using the Illumina MiSeq and Pacbio RSII pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…2019; Shang et al . 2019). Besides ICEs, integrative mobilizable elements likely play a major role in the horizontal transfer of AMR genes in S. suis (Libante et al .…”
Section: Discussionmentioning
confidence: 99%
“…2019; Shang et al . 2019). Besides ICEs, integrative mobilizable elements likely play a major role in the horizontal transfer of AMR genes in S. suis (Libante et al .…”
Section: Discussionmentioning
confidence: 99%
“…Amphenicol resistance is mediated by several mechanisms in S. suis . The first is the Cfr rRNA methyl-transferase encoded by the cfr gene as described above [ 37 ], and the second is a chloramphenicol acetyl-transferase mediated by the cat gene [ 57 ]. S. suis antimicrobial resistance genes also encode efflux proteins of the major facilitator superfamily that transport amphenicol-chloramphenicol outside the bacteria, in particular the FexA protein composed of 14 transmembrane helices [ 24 , 37 , 44 , 58 ].…”
Section: Mechanisms Of Antimicrobial Resistance (Amr) and Resistance Genes Found In S Suismentioning
confidence: 99%
“…S. suis antimicrobial resistance genes also encode efflux proteins of the major facilitator superfamily that transport amphenicol-chloramphenicol outside the bacteria, in particular the FexA protein composed of 14 transmembrane helices [ 24 , 37 , 44 , 58 ]. S. suis can also harbor the optr A gene that encodes an ATP-binding cassette (ABC) transporter [ 44 , 57 , 59 ] ( Figure 1 ).…”
Section: Mechanisms Of Antimicrobial Resistance (Amr) and Resistance Genes Found In S Suismentioning
confidence: 99%
“…In Streptococcus suis pig isolates, optrA has been recently described within a novel composite IS1216E-araC-optrA-hp-catpC 194 -IS1216E transposon integrated on a phage similar to Φm46.1 [73]. optrA was identified in prophages and ICEs only in Streptococcus suis [32,73,74], but the mobilization of optrA through phage-mediated transduction cannot be discarded also in enterococci. Wang et al [75] also recently demonstrated by a metagenomic approach in swine feedlot wastewater samples that phages were more likely to harbor ABC transporter family and ribosomal protection genes including optrA.…”
Section: Comparison Of Chromosomal Optra-carrying Contigsmentioning
confidence: 99%